2020
DOI: 10.3390/ijms21218097
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Rpn4 Links the Proteasome and DNA Repair via RAD52 Regulation

Abstract: Environmental and intracellular factors often damage DNA, but multiple DNA repair pathways maintain genome integrity. In yeast, the 26S proteasome and its transcriptional regulator and substrate Rpn4 are involved in DNA damage resistance. Paradoxically, while proteasome dysfunction may induce hyper-resistance to DNA-damaging agents, Rpn4 malfunction sensitizes yeasts to these agents. Previously, we proposed that proteasome inhibition causes Rpn4 stabilization followed by the upregulation of Rpn4-dependent DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 82 publications
1
8
0
Order By: Relevance
“…Therefore, this experiment can be considered as a model study of the effect of RNR inhibitors on the phenotype of cancer hyper resistance to DNA-damaging drugs. As previously shown, YPL cells are more viable when chronically exposed to 4-NQO [ 11 , 13 ]. Thus, if increased RNR activity is involved in cell resistance to 4-NQO, its inhibition may cause reduced YPL growth under 4-NQO stress.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…Therefore, this experiment can be considered as a model study of the effect of RNR inhibitors on the phenotype of cancer hyper resistance to DNA-damaging drugs. As previously shown, YPL cells are more viable when chronically exposed to 4-NQO [ 11 , 13 ]. Thus, if increased RNR activity is involved in cell resistance to 4-NQO, its inhibition may cause reduced YPL growth under 4-NQO stress.…”
Section: Resultsmentioning
confidence: 84%
“…Despite this, we and other researchers have previously shown that proteasome mutant strains of yeast are hyper-resistant to several DNA-damaging agents, including 4-NQO [ 11 , 12 ]. Previously, we showed that increased levels of Rpn4-dependent DNA repair genes cause hyper resistance to 4-NQO in proteasome mutants [ 11 , 13 ]. Acquiring resistance should be accompanied by increased levels of proteins managing DNA reparation/replication, as well as degradation of damaged proteins.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations